Effects of extending paid parental leave on children's socio-emotional skills and well-being in adolescence - Mikkel Aagaard Houmark; Cecilie Marie Løchte Jørgensen; Ida Lykke Kristiansen; Miriam Gensowski (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
We study how children's socio-emotional skills and well-being in adolescence are affected by an increase in the duration of parental care during infancy. Exploiting a Danish reform that extended paid parental leave in 2002 and effectively delayed children's entry into formal out-of-home care, we show that longer leave increases adolescent well-being, conscientiousness and emotional stability, and reduces school absenteeism. The effects are strongest for children of mothers who would have taken short leave in absence of the reform. This highlights how time spent with a parent is particularly productive during very early childhood.
Keywords: J13; J18; J24; I31; 330; Parental Leave; Early Childhood; Skill Formation; Parental Investments; SocioEmotional Skills; Personality; Well-Being; Adolescence